“Prince Edward Island’s unique ‘brotherly love’ community”: Faith and Family, Communalism and Commerce in B. Compton Limited, 1909-1947 - Brouwer, Ruth (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2016)
Imbued with the millenarian teachings of a maverick 19th-century Island clergyman and with a desire to provide communally for a close-knit kin group that had experienced economic hardship at the dawn of the 20th century, B. Compton Limited – a utopian community on Prince Edward Island – briefly became an object of widespread interest in the context of the Depression. A visiting rural sociologist noted, for instance, its members’ eccentricity while affirming their strong ties within the Island’s social fabric. This article explores the community’s background, the factors that held it together, and the wartime changes that culminated in its formal dissolution in 1947.